Skilled birth attendant services in Nepal: overcoming barriers to utilization. - Choulagai,Bishnu Prasad (2017)
ABSTRACT: Background :Skilled birth attendants (SBAs) provide important services that improve maternal and newborn health and reduce maternal and newborn mortality. Utilization and coverage of SBA services reveal wide disparities between the rural and urban areas of Nepal. Aims :This thesis aimed to identify the barriers to SBA service utilization in Nepal and develop and test a community intervention to address those barriers and increase service utilization. Methods :Mixed-methods research was applied to identify barriers to SBA service utilization, followed by an intervention to address those barriers. Status of SBA service utilization and associated factors were investigated using crosssectional surveys in rural settings of mid- and far-western Nepal and in an urban setting in the Jhaukhel-Duwakot Health Demographic Surveillance Site, Bhaktapur, Nepal. The qualitative study explored perceptions of service users and providers regarding barriers to SBA service utilization and suggestions to overcome those barriers. After identifying such barriers, we designed, implemented, and evaluated a five-component community intervention. The intervention was designed as a cluster-randomized controlled trial involving 36 Village Development Committees. Results: Cross-sectional surveys showed that the utilization of SBA services at delivery was 48% in mid- and far-western Nepal and 93.1% in the JD-HDSS. Distance to a health facility and inadequate transport were major barriers to SBA service utilization. Similarly, inadequate knowledge of women and their families regarding the importance of SBA services and low prioritization of birth care hindered such utilization. Women's knowledge of danger signs of pregnancy and delivery and their educational attainment were determining factors in SBA service utilization. Women who had completed at least four antenatal care (ANC) visits were more likely to use skilled birth care. Our one-year intervention was associated with increased use of skilled birth care services (OR=1.57; CI: 1.19-2.08). However, there was no significant association of the intervention with the use of ANC services. Conclusions :There is an urgent need to increase the utilization of SBA services in rural areas of Nepal and address the rural-urban gap in such utilization. An effective intervention for increasing SBA utilization includes mobilizing active community groups, improving service quality and physical infrastructure at health facilities, providing adequate SBAs at health facilities, and implementing longer-term and repeated interventions. Community mobilization efforts are effective, but such efforts require supervision and support to ensure quality of the implementation. Keywords: Maternal health, newborn health, skilled birth attendant, implementation research, health services research, mixed-methods research, clusterrandomized controlled trial, evaluation, Nepal